Bone Marrow Mesenchymal Stem Cells Enhance the Differentiation of Human Switched Memory B Lymphocytes into Plasma Cells in Serum-Free Medium - Guillaume Bonnaure; Catherine Gervais-St-Amour; Sonia Néron (Journal of Immunology Research)
The differentiation of human B lymphocytes into plasma cells is one of the most stirring questions with regard to adaptive immunity. However, the terminal differentiation and survival of plasma cells are still topics with much to be discovered, especially when targeting switched memory B lymphocytes. Plasma cells can migrate to the bone marrow in response to a CXCL12 gradient and survive for several years while secreting antibodies. In this study, we aimed to get closer to niches favoring plasma cell survival. We tested low oxygen concentrations and coculture with mesenchymal stem cells (MSC) from human bone marrow. Besides, all cultures were performed using an animal protein-free medium. Overall, our model enables the generation of high proportions of CD38+CD138+CD31+ plasma cells (≥50%) when CD40-activated switched memory B lymphocytes were cultured in direct contact with mesenchymal stem cells. In these cultures, the secretion of CXCL12 and TGF-β, usually found in the bone marrow, was linked to the presence of MSC. The level of oxygen appeared less impactful than the contact with MSC. This study shows for the first time that expanded switched memory B lymphocytes can be differentiated into plasma cells using exclusively a serum-free medium.